Digital Financial Inclusion, Digital Financial Literacy, and Financial Self-Efficacy - Sutarmi Sutarmi; Tastaftiyan Risfandy; Inas Nurfadia Futri (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2026)
Digital financial inclusion has become progressively viewed as an essential instrument to advance economic development that is both inclusive and sustainable. However, the behavioral factors influencing its adoption remain poorly understood. This research examines the variables shaping of digital financial inclusion among communities in Surakarta, Indonesia, emphasizing the effect of digital financial literacy and financial self-efficacy. Survey data from 258 purposively selected respondents were analyzed using logistic regression in STATA software. The results indicate that digital financial literacy serves as a key determinant in shaping financial self-efficacy and encourages individual participation in digital financial services. However, financial self-efficacy does not directly influence digital financial inclusion or act as a mediating variable. Additional findings reveal that increasing age tends to reduce the extent of digital financial inclusion, whereas income is positively related to it, and education level is inversely related to it. Digital financial literacy has been shown to be a key determinant, compared to psychological factors, in expanding digital financial inclusion. Therefore, strengthening education and community empowerment programs is crucial for building an inclusive digital financial ecosystem.Kata kunci: